2020
DOI: 10.35473/jgk.v12i27.60
|View full text |Cite
|
Sign up to set email alerts
|

Hubungan Panjang Badan Lahir, Berat Badan Lahir Dan Pemberian Asi Eksklusif Terhadap Kejadian Stunting Pada Baduta Usia 7-24 Bulan Di Desa Wonorejo Kecamatan Pringapus Kabupaten Semarang

Abstract: Latarbelakang : Stunting adalah masalah kurang gizi kronis yang disebabkan oleh asupan gizi yang kurang dalam waktu cukup lama akibat pemberian makanan yang tidak sesuai dengan kebutuhan gizi. Berat badan lahir, panjang badan lahir, pemberian ASI, usia kehamilan, pola asuh ibu, sanitasi dan kesehatan lingkungan merupakan faktor terjadi stunting. Tujuan : Untuk mengetahui hubungan panjang badan lahir, berat badan lahir dan pemberian ASI eksklusif dengan kejadian stunting pada baduta usia 7-24 bulan di Des… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 0 publications
0
2
0
2
Order By: Relevance
“…The results of this study are in line with research in Wonorejo, Semarang, showing that short birth length was 34 children (97.1%), while normal birth length was 12 children (30.8%), so it can be concluded that the prevalence of stunting in toddlers at short birth body length is higher when compared to normal birth length. Based on the risk estimate test, the OR = 76,500 was obtained, so the results of this study show that toddlers with short birth lengths are at 75.5 times greater risk of experiencing stunting compared to toddlers with normal birth lengths (Andini et al, 2020).…”
Section: Birth Length With Stuntingmentioning
confidence: 76%
“…The results of this study are in line with research in Wonorejo, Semarang, showing that short birth length was 34 children (97.1%), while normal birth length was 12 children (30.8%), so it can be concluded that the prevalence of stunting in toddlers at short birth body length is higher when compared to normal birth length. Based on the risk estimate test, the OR = 76,500 was obtained, so the results of this study show that toddlers with short birth lengths are at 75.5 times greater risk of experiencing stunting compared to toddlers with normal birth lengths (Andini et al, 2020).…”
Section: Birth Length With Stuntingmentioning
confidence: 76%
“…If the mother suffers from a lack of energy and protein during pregnancy, there is a risk that the baby will be 48 cm long. Andini, 2019 added that babies born with a short body length were 75.5 times more likely to suffer from stunted growth (Andini, Maryanto, & Mulyasari, 2020;Supariasa, Bakri, & Fajar, 2012, 2016.…”
Section: Discussionmentioning
confidence: 99%
“…Hasil penelitian ini sesuai dengan hasil penelitian Sutrio dan Lupiana (2019) di Kabupaten Pesawaran Provinsi Lampung yang menghasilkan data sebanyak 100% anak dengan berat lahir kategori BBLR mengalami stunting dan 78,1% anak dengan panjang lahir kategori pendek mengalami stunting. Penelitian ini memperkuat temuan dari penelitian sebelumnya yang menunjukkan adanya korelasi antara berat lahir rendah dan panjang lahir pendek dengan kejadian stunting di berbagai daerah di Indonesia (Ayuningtyas et al, 2020;Andini et al, 2020;Hanifa dan Mon, 2021).…”
Section: Gambar 1 Prosedur Pengambilan Subjekunclassified